Kemampuan Komunikasi Matematis Siswa SMP ditinjau dari Gaya Belajar - Anggani, Nadiva Dwi; Fachriza, Hilda; Simanjuntak, Afnita; Herman, Tatang; Hasanah, Aan (Universitas Serang Raya, 2024)
Taking into account auditory, visual, and kinesthetic learning modalities, this research animed to evaluate students mathematical communication abilities on the subject of Two Variable Linear Equation Systems. This qualitative study surveyed six junior high school students from the city of Sukabumi. The tools used for this study were a written exam to evaluate mathematical communication abilities and a learning style questionnaire. Mathematical communication skills are the basis of the learning style questionnaire. These skills include the ability to draw connections between mathematical ideas and real word objects, images, and diagrams to explain mathematical concepts, situations, and relationships in writing and to express events or ideas using mathematical symbols or language. Communication abilities are excellent among students with low visual learning styles, as are those with high visual learning styles, according to the study’s findings. The communication abilities of pupils whose learning style is mostly auditory are good, while those whose learning style is predominantly visual are poor. The same holds true for students communication abilities, those who learn best via movement tend to have excellent ones, while those who learn best by sitting still tend to struggle. Knowing one’s own learning style is crucial for pupils to enhance their mathematics communication abilities